2020
DOI: 10.1021/acsmedchemlett.9b00633
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Indazole-Based GSK-3 Inhibitors with Mitigated hERG Issue and In Vivo Activity in a Mood Disorder Model

Abstract: Bipolar disorders still represent a global unmet medical need and pose a requirement for novel effective treatments. In this respect, glycogen synthase kinase 3β (GSK-3β) aberrant activity has been linked to the pathophysiology of several disease conditions, including mood disorders. Therefore, the development of GSK-3β inhibitors with good in vivo efficacy and safety profile associated with high brain exposure is required. Accordingly, we have previously reported the selective indazole-based GSK-3 inhibitor 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…16). 93 Their studies suggested that the replacement of the (2-methoxyethyl)-4methylpiperidine group by oxanyl, oxolanyl, thiolanedionyl and thianedionyl groups reduced the lipophilicity of the resultant derivatives (33)(34)(35)(36)(37)(38)(39)(40)(41) and led to improved selectivity towards the human ether-à-go-go-related dene (hERG) by 41-500 fold compared to compound 40. Further, replacement of the diuorophenyl moiety with polar pyridinyl and alkoxysubstituted pyridinyl groups led to compounds (44a-f) with promising activities (hERG IC 50 > 40 mM), except for compounds 44b and 44c (hERG IC 50 ¼ 0.86 and 5.70 mM, respectively).…”
Section: (V) Pan-tropomyosin Receptor Kinase (Pan-trk) Inhibitorsmentioning
confidence: 99%
“…16). 93 Their studies suggested that the replacement of the (2-methoxyethyl)-4methylpiperidine group by oxanyl, oxolanyl, thiolanedionyl and thianedionyl groups reduced the lipophilicity of the resultant derivatives (33)(34)(35)(36)(37)(38)(39)(40)(41) and led to improved selectivity towards the human ether-à-go-go-related dene (hERG) by 41-500 fold compared to compound 40. Further, replacement of the diuorophenyl moiety with polar pyridinyl and alkoxysubstituted pyridinyl groups led to compounds (44a-f) with promising activities (hERG IC 50 > 40 mM), except for compounds 44b and 44c (hERG IC 50 ¼ 0.86 and 5.70 mM, respectively).…”
Section: (V) Pan-tropomyosin Receptor Kinase (Pan-trk) Inhibitorsmentioning
confidence: 99%
“…INDZ derivatives 1-6 were synthesized as previously described [17][18][19], whereas imidazo[1,5-a] pyridines 7-18 were prepared according to the linear synthetic routes depicted in Schemes 1 and 2. Specifically, IMID 1 derivatives 7-10 and 12 were obtained in a four-step synthesis starting from the commercially available 7-bromoimidazo[1,5-a]pyridine (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…Specifically, IMID 1 derivatives 7-10 and 12 were obtained in a four-step synthesis starting from the commercially available 7-bromoimidazo[1,5-a]pyridine (Scheme 1). 7-bromoimidazo[1,5-a]pyridine underwent Vilsmeier-Haack reaction in the presence of DMF and phosphorus oxychloride to provide the corresponding aldehyde (19). Subsequent silver nitrate-mediated oxidation led to the carboxylic acid 20, which was then coupled to 1-[1-(2-methoxyethyl)piperidin-4-yl]methanamine and 1-(oxan-4-yl)methanamine under standard carboxylic acid-amine coupling reaction to afford amides 21 and 22, respectively.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations